2008
DOI: 10.1080/13887890.2008.9748312
|View full text |Cite
|
Sign up to set email alerts
|

European Odonata as hosts ofForcipomyia paludis(Diptera: Ceratopogonidae)

Abstract: The biting midge Forcipomyia (Pterobosca) paludis is the only ceratopogonid species known to parasitise Odonata imagines in Europe. In this study, based mainly on the analysis of about 200 photographically documented cases, data on host species, parasite load and undisturbed position on the odonate body were analysed. The list of hitherto known hosts is extended significantly to include 55 Odonata species. The records date from mid-May to the beginning of August. Most data originate from southern France, Switz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…On photographs taken under natural conditions most female individuals of Forcipomyia paludis are located and positioned on the dragonflies' wings as described in earlier studies (e.g., Martens et al 2007;Manger 2021). Obviously, the body posture and the slightly tilted head position allow an easier piercing of the vein at its lateral base (cf.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On photographs taken under natural conditions most female individuals of Forcipomyia paludis are located and positioned on the dragonflies' wings as described in earlier studies (e.g., Martens et al 2007;Manger 2021). Obviously, the body posture and the slightly tilted head position allow an easier piercing of the vein at its lateral base (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Field observations and in situ photography, focused on various odonate species infested with Forcipomyia paludis (Macfie 1936), were conducted in southern France (Saint-Martin-de-Crau), Switzerland (Uster, Hinwil) and Georgia (Sartichala), at localities where infested odonates had been known (Martens et al 2007;Wildermuth 2012;Wildermuth et al 2019). Samples of F. paludis specimens attached to wing fragments of Cordulegaster boltonii (Donovan, 1807) were air-dried.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some other species placed in different subgenera of Forcipomyia are also found on wings of odonates (Borkent, 2012). In Europe, Forcipomyia paludis is known to attack more than 70 species of dragonflies (Martens et al, 2007;Vinko et al, 2017;Cordero-Rivera et al, 2019). In Asia, there are several species associated to odonates like F. latipes, F. fidens (Macfie, 1936a), F. aerobates (Macfie, 1936b), F. tokunagai (Naraoka, 1999) and F. debenhamae (Orr and Cranston, 1997), and a review of pictures of odonates from Cambodia revealed a high incidence of one unidentified species of Forcipomyia (Kosterin et al, 2012).…”
Section: The First Record Of Parasitism By Forcipomyia (Diptera: Ceramentioning
confidence: 99%